2018
DOI: 10.1016/j.watres.2018.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous microbial vanadium (V) reduction and denitrification in groundwater using hydrogen as the sole electron donor

Abstract: Groundwater co-contaminated by vanadium (V) (V(V)) and nitrate requires efficient remediation to prevent adverse environmental impacts. However, little is known about simultaneous bio-reductions of V(V) and nitrate supported by gaseous electron donors in aquifers. This study is among the first to examine microbial V(V) reduction and denitrification with hydrogen as the sole electron donor. V(V) removal efficiency of 91.0 ± 3.2% was achieved in test bioreactors within 7 d, with synchronous, complete removal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(33 citation statements)
references
References 64 publications
0
31
2
Order By: Relevance
“…These members of the microbial community accumulated in our study and were also found in the vanadium‐contaminated environment (Cao et al, ). They potentially participate in V(V) reduction because vanadium is a redox‐sensitive metal similar to selenium and chromium (Jiang et al, ). In the vertical soil profile, Acidobacteria that accounted for a large proportion of the microbial population can adapt to vanadium‐polluted environments (Cao et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These members of the microbial community accumulated in our study and were also found in the vanadium‐contaminated environment (Cao et al, ). They potentially participate in V(V) reduction because vanadium is a redox‐sensitive metal similar to selenium and chromium (Jiang et al, ). In the vertical soil profile, Acidobacteria that accounted for a large proportion of the microbial population can adapt to vanadium‐polluted environments (Cao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparative evaluation of the performance of dissolved organic carbon sources shows that acetate supports highly efficient V(V) bio‐reduction (Liu et al, ). Oxidation of gaseous and solid electron donors, such as hydrogen and elemental sulfur (Jiang et al, ; Zhang, Zhou, et al, ; Zhang, Qui, et al, ), can also be coupled to V(V) bio‐reduction without residual organics. Furthermore, coexisting common electron acceptors in groundwater, such as nitrate and sulfate, can decrease the efficiency of V(V) bio‐reduction since they are more efficient electron acceptors (Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium, a redox-sensitive metal, widely occurring in the Earth's crust, is employed in metallurgy, manufacturing, and petroleum refining industries [2], and is an efficient catalyst in the selective catalytic reduction of nitrogen oxides in exhaust gases [3]. Dissolution of vanadium-rich rocks and anthropogenic activities lead to the presence of vanadium in groundwater [4,5]. For example, mining and smelting processes discharge vanadium into soil, after which vanadium can enter aquifers through infiltration [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, groundwater contaminants are not unique in most cases; concurrent contamination by various oxidized contaminants such as nitrate and chromate is increasingly commonplace . Human activities including electroplating and alloy production have had profound impacts on the discharge of chromium (Cr) into aquifers .…”
Section: Introductionmentioning
confidence: 99%
“…4 However, groundwater contaminants are not unique in most cases; 7 concurrent contamination by various oxidized contaminants such as nitrate and chromate is increasingly commonplace. 7,8 Human activities including electroplating and alloy production have had profound impacts on the discharge of chromium (Cr) into aquifers. 9 Excessive intake of hexavalent chromate [Cr(VI)] (0.1 mg L −1 of MCL in drinking water proposed by U.S. EPA) can cause carcinogenic, teratogenic and mutagenic effects in animals and humans.…”
Section: Introductionmentioning
confidence: 99%